2016
DOI: 10.1007/s10511-016-9457-2
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar Extinction

Abstract: Key words: interstellar extinction: reddening: interstellar dust particles: characteristics and properties of the Milky Way galaxy.This review describes our current understanding of interstellar extinction. This differ substantially from the ideas of the 20th century. With infrared surveys of hundreds of millions of stars over the entire sky, such as 2MASS, SPITZER-IRAC, and WISE, we have looked at the densest and most rarefied regions of the interstellar medium at distances of a few kpc from the sun. Observat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 101 publications
0
18
0
Order By: Relevance
“…Hence, this envelope is elongated between l ≈ 40 • and 250 • and, thus, nearly follows a wide extension of the Local Bubble at low latitudes of the 2 nd and 6 th octants, evident in Fig. 7 (a) and known as the Local interstellar tunnel, or the Great tunnel (Welsh 1991;Gontcharov 2012b). It consists of the Cygnus Cavities, Local Bubble, and CMa tunnel (see LVV, figure 1).…”
Section: Spatial Variations Of Position Anglementioning
confidence: 84%
“…Hence, this envelope is elongated between l ≈ 40 • and 250 • and, thus, nearly follows a wide extension of the Local Bubble at low latitudes of the 2 nd and 6 th octants, evident in Fig. 7 (a) and known as the Local interstellar tunnel, or the Great tunnel (Welsh 1991;Gontcharov 2012b). It consists of the Cygnus Cavities, Local Bubble, and CMa tunnel (see LVV, figure 1).…”
Section: Spatial Variations Of Position Anglementioning
confidence: 84%
“…They intersect at a large angle and near the directions to the Galactic Centre and anticentre. As a result, two parts of the Zodiacal dust belt are projected to the most dense parts of the dust layer of the Gould Belt at l = 345 • , b = 19 • and l = 165 • , b = −19 • (Gontcharov 2012b, table 4), (see also Gontcharov 2009Gontcharov , 2016b. Other parts of the Zodiacal dust belt are projected to the high latitude areas (for example, ecliptic at the longitudes 155 • < λ < 205 • and −25 • < λ < 25 • , i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The map is normalized to the E(B − V) reddening (which is cumulative as well) using the color excess of 389 elliptical galaxies with E(B − V) < 0.2 mag assuming the relation (1) and the extinction laws from Cardelli et al (1989) andO'Donnell (1994). A brief review of the main systematic errors of the SFD map with related references can be found in Gontcharov (2016b).…”
Section: The Schlegel Finkbeiner and Davis (1998) Mapmentioning
confidence: 99%